Ethics of sound quality in online teaching, learning and conferencing: perspectives gained during the covid pandemic - Musib, Ahmad Faudzi; Meddegoda, Chinthaka Prageeth; Jähnichen, Gisa; Mei, Xiao (International Association of Sound and Audiovisual Archives (IASA) Journal, 2023)
Recent developments in using audiovisual software for teaching and learning are very challenging in terms of achieving a minimum of audio and visual quality. This article will focus on the correlation between visibility and audio quality of content transmission, as well as ways of making specific experiences in choosing tools and publicly accessible methods preservable. Each expert provides their personal and professional experiences concerning audio processing applied to an online learning environment, the challenges of teaching singing online, and the audiovisual preparation of online conferences. The experts work in the audiovisual archives field and are all connected through their work advocating for small-scale archives in Asia. They are frequent contributors to the IASA Journal. In this article, their most recent perspectives with ethics in sound quality will be the centre of the exchange of ideas.